Implementing an electronic learning management system for an Ophthalmology residency program. Issue 1 (December 2016) - Mahoney, Nicholas; Boland, Michael; Ramulu, Pradeep; Srikumaran, Divya
Abstract Background Medical educators, residents and administrators have increasing access to a large quantity of electronic resources. This content can augment and improve our teaching methods but can be difficult to consolidate and present. A multitude of electronic learning management systems are available to help organize and serve this content though never with small residency programs as the target userbase. As our residency program in Ophthalmology looked to consolidate our electronic resources and update our education methods, we evaluated and built an electronic learning management platform. Results Faculty were interviewed to determine features they would find useful in curriculum management system and then various systems were investigated for features, cost and ease of use. Conclusions Our solution has been both cost-effective and successful. Resident satisfaction is high and faculty utilization has been increasing. We present many customizations that increased success. Consideration of the specific needs of a program is paramount to choosing a cost effective solution that will be well received.